Input–output life cycle environmental assessment of greenhouse gas emissions from utility scale wind energy in the United States. (February 2016) - Kumar, Indraneel; Tyner, Wallace E.; Sinha, Kumares C.
Abstract: Wind energy is an emerging source for renewable energy. This article presents an application of the economic input–output life cycle assessment (EIO-LCA) to estimate the greenhouse gas (GHG) emissions through the life cycle of wind energy farms in a state. The EIO-LCA incorporates manufacturing, installation, operation and maintenance, and decommissioning of the wind turbine over its life cycle period. In doing so, the study demonstrates that O&M and decommissioning of infrastructure with a longer life period can be considered to assess the total environmental impacts. The life cycle costs of wind turbine installation in Indiana is used in this study. The uncertainty in wind energy production, and hence the variability in GHG emission intensities in metric tons per gigawatt hour (GWh), is demonstrated by using the Monte Carlo simulation. The research finds that wind energy production is not entirely GHG emission-free if all the costs and life cycle stages are considered. Emission estimates have uncertainty, and O&M and decommissioning can add up to 200 metric tons of GHG emissions in CO2 e per wind turbine life cycle. The regional EIO-LCA can be a helpful tool to determine strategies for state compliance to initiatives, such as the Clean Power Plan. Highlights: We include O&M and decommissioning stages into the EIO-LCA of wind turbine. Both the stages can add up to 200 metric tons of GHG CO2 e per turbine life cycle. Mean GHG emission rate per turbine is 19 and range is 15–29 g CO2 e per KWh. Emission intensities can have uncertainties dependent on region-specific traits. Regional EIO-LCA can be useful for state compliance to the Clean Power Plan.